2017
DOI: 10.1073/pnas.1620558114
|View full text |Cite
|
Sign up to set email alerts
|

AXL-dependent infection of human fetal endothelial cells distinguishes Zika virus from other pathogenic flaviviruses

Abstract: Although a causal relationship between Zika virus (ZIKV) and microcephaly has been established, it remains unclear why ZIKV, but not other pathogenic flaviviruses, causes congenital defects. Here we show that when viruses are produced in mammalian cells, ZIKV, but not the closely related dengue virus (DENV) or West Nile virus (WNV), can efficiently infect key placental barrier cells that directly contact the fetal bloodstream. We show that AXL, a receptor tyrosine kinase, is the primary ZIKV entry cofactor on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
163
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(176 citation statements)
references
References 55 publications
10
163
1
2
Order By: Relevance
“…Alternatively, ZIKV may directly infect the endothelial cells or choroid plexus epithelial cells, disrupt the BBB, and enter the CNS. Since the TAM receptor AXL makes endothelial cells susceptible to ZIKV infection (50)(51)(52), access of the mutant ZIKVs encoding nonglycosylated E protein to the CNS might be compromised due to their inability to infect these cells. Since WNV disrupts expression of or signaling by IFN- (53) and also uses the Toll-like receptor 3-dependent immune response (54) to gain entry into the CNS, it is possible that ZIKV may employ similar or yet unknown mechanisms to facilitate its entry into the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, ZIKV may directly infect the endothelial cells or choroid plexus epithelial cells, disrupt the BBB, and enter the CNS. Since the TAM receptor AXL makes endothelial cells susceptible to ZIKV infection (50)(51)(52), access of the mutant ZIKVs encoding nonglycosylated E protein to the CNS might be compromised due to their inability to infect these cells. Since WNV disrupts expression of or signaling by IFN- (53) and also uses the Toll-like receptor 3-dependent immune response (54) to gain entry into the CNS, it is possible that ZIKV may employ similar or yet unknown mechanisms to facilitate its entry into the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…In the placenta, the maternal blood and fetal blood are separated by placental barrier cells, including trophoblasts and endothelial cells. Recent studies have demonstrated that fetal endothelial cells or human umbilical vein endothelial cells (HUVEC) are permissive for ZIKV infection, making HUVEC a key cell model for ZIKV studies (23,24).…”
mentioning
confidence: 99%
“…Our study demonstrates that PKI potently suppresses ZIKV replication and, hence, is a potential candidate for therapeutic application. [23][24][25]. To confirm that HUVEC were permissive for infection with all the ZIKV strains used in the study, we first evaluated the infectivity and replication of ZIKV in HUVEC.…”
mentioning
confidence: 99%
“…Considerando que en este trabajo se utilizó el prototipo de proteína E del virus ZIKV (entrada PDB 5I6Z7), y dada la existencia de diferentes aislamientos del ZIKV procedentes de Latinoamérica y Asia, es importante profundizar en las mutaciones o variantes de la secuencia y la estructura molecular del E-ZIKV que modifiquen el dominio hidrofóbico interno, el bucle de fusión u otros elementos estructurales que pueden sufrir modificación posterior a la traducción, incluidos los sitios de glucosilación (53), con lo cual se produciría un efecto en la capacidad de infección del ZIKV a otros tipos de células específicas (2,54,55).…”
Section: Discussionunclassified